Pengaruh Earning Before Tax dan interest expense terhadap Net Income pada sektor Perbankan - Ginting, Rasinta Ria; Hutagalung, Galumbang; Simorangkir, Enda Noviyanti (Owner : Riset dan Jurnal Akuntansi, 2024)
The research was conducted to comprehensively determine the effect of interest expense and earnings before tax on net income. This study uses a quantitative descriptive approach, with a population of SOEs engaged in financial services represented by PT Bank Rakyat Indonesia (Persero) Tbk. from several banks in Indonesia. The sampling technique uses a probability sample with a purposive sampling method. In addition, the sample data from this company were 20 from the last five years of PT Bank Rakyat Indonesia (Persero) Tbk's financial reporting. which includes Q1, Q2, Q3, and Q4 (Audited). Data analysis using SmartPLS4 software with the study results showed that the interest expense variable significantly affects net income, and earnings before tax significantly affect net income. However, other factors affect the value of net income, which tends to increase, like pro forma profit. Thus H1, H2, and H3 are accepted, which means that there is a significant influence between interest expense, earnings before tax, and net income.